Association of Physical Activity and Academic Performance in Schoolchildren of Nepal (Baltic Journal of Sport and Health Sciences, 2017)
Background.  There  is  growing  interest  in  the  association  between  physical  activity  (PA)  and  academic performance (AP) in children, especially in the developing world. However, no in-depth study of such kind has yet been undertaken in Nepal. Therefore, this study was carried out to determine if there is correlation between PA and AP in secondary schoolchildren in Nepal. Methods. A crosssectional study was carried in four schools of Nepal. Two schools (one private and one public) were randomly selected from two different districts. Physical activity and academic performance levels of students were obtained via questionnaires and Pearson’s correlation was done to determine any association. Results. Our study showed a significant correlation between physical activity and academic performance in the study population. The correlation was significant for male students, students from rural and urban areas and from public schools. However, there was no significant correlation in the female population and students of private schools. We also observed a significant difference in the physical activity performed by male versus female students (male > female), along with a significant difference in their academic performance (male > female). Further analysis of correlation on the basis of gender showed that physical activity of male students was significantly correlated with the academic performance irrespective of the location and type of school. However there was no such correlation in the female students. Conclusion. Our study found that male students who were physically active showed positive correlation between physical activity and academic performance while no such correlation was found in the female students.Keywords: physical activity, academic performance, schoolchildren, Nepal.